(The literary contributions of Al-Tawhidi in the history of public life in Baghdad 310 – 414 AH / 922 – 1023AD) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Despite the efforts of the Abbasid historians (during the Buyid rule 334 – 447 AH / 946 – 1055 AD) to chronicle the events of that era, with the progress of codification methods in governance, public and local history, biography, and translations, but they wrote down the prominent political events, and under the supervision of the rulersWhile literary sources were far from the rulers control and were preoccupied with the history of the daily life of the common people, they recorded important events in political, social, economic and intellectual affairsAmong these writers was Tawhidi in his book Enjoyment and Friendship, which was distinguished   in its accurate history of the daily life of the public